Examining the relationship between online distribution channels and tourist satisfaction and loyalty - Paula Antón Maraña; Julio César Puche Regaliza; Pablo Arranz Val; Santiago Aparicio Castillo (Tourism & Management Studies)
Although the Internet and e-commerce have contributed positively to the tourism sector, there is not much empirical research on the transformation of distribution channels or that considers the use of the Internet in travel planning as an antecedent of tourist satisfaction and loyalty. This paper aims to test the influence of online distribution channels in trip planning by tourists on their general satisfaction level and their loyalty towards the destination and to differentiate the profile of digital and traditional tourists. Quantitative research techniques are used to analyse the dataset of 1,387 surveys of tourists visiting the province of Burgos, Spain. Among those surveyed, 65% search for information online and 54% book or pay for services online. According to ordinal regression analysis, the use of online channels does not significantly influence the level of satisfaction, but according to binary logistic regression, it does significantly influence loyalty. The findings provide valuable information for developing marketing strategies in tourism organisations and support decision-makers in creating competitive tourism destinations that are resilient to the demographic challenge of depopulation.